Establishment Of A Sakinah Family Through The Klinik Nikah Medan As A Pre-Marriage Guidance Institution - Batubara, Alvi Mawaddah; Huda, Nurul; Yazid, Imam (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
This research was motivated by the results of the researchers' initial observations regarding the premarital guidance provided by the Medan Marriage Clinic to the participants. This study aims to determine the main objectives of establishing the Medan Marriage Clinic, the system of providing premarital guidance carried out by the Medan Marriage Clinic, the suitability of premarital guidance at the Medan Marriage Clinic with the provisions of the Directorate General of Islamic Community Guidance in 2018, as well as the effectiveness of the Medan Marriage Clinic in forming a happy family. sakinah. In this study, researchers used descriptive qualitative methods with observation and interview data collection techniques. This type of research is field research (field research). The number of respondents in this study were 5 founders of the Medan Marriage Clinic and 30 alumni of the Marriage Clinic. Based on the results of the research, the guidance system implemented by the Medan marriage clinic is quite good with a lecture system in 12 meetings for a period of 3 months, as for the material, Mindset and Intentions for Marriage, Premarital Health, Stages of Choosing a Match, Ta'aruf, Khitbah and Dowry , KUA Administration, Walimah Fiqh, Jima' Fiqh, Fiqh of Livelihoods, Financial Management, Building Communication, Family Conflict Management, Fiqh of Divorce and Ruju', Consolidation Towards Marriage. With lecture and question and answer method. Based on observations that have been made that the provision of guidance at the Medan Marriage Clinic is in accordance with the provisions of the Directorate General of Islamic Community Guidance in 2018 starting from methods, vision, mission, and materials